E.B. O'Callaghan, Laws and Ordinances of New Netherland, 1638-1674, at 138 (1868); N.Y. Col. MSS, XVI. 31 - (:unkn) unknown (My University, 1652)
Ordinance Of The Director And Council Of New Netherland Against Firing At Partridges Or Other Game Within The Limits Of New Amsterdam: Therefore the Honorable Director General and Council, in order to prevent accidents, expressly forbid and interdict all persons henceforward firing within the jurisdiction of this city or about the Fort, with any guns at Partridges or other Game that may by chance fly within the city, on pain of forfeiting the gun and a fine at the discretion of the Judge, to be applied one-third to the Poor, one-third to the Church and one-third to the Officer.
Keywords: HUNTING REGULATION